Pepper Harvest Mechanism - Tekgüler, Ali; Karaköse, Tuğba (My University, 2018)
Due to increased food need, plant cultivation issue has started to come up more often. As in all stagesof plant cultivation, the importance of harvesting is also increasing. Due to the consequences of shifting theworkforce to different areas in the developing world, tools and machines manufactured for use in agricultureneed to be mechanized with greater efficiency. Studies on pepper harvesting mechanisms have been going onfor many years. Although mechanisms are operated at certain harvest effectiveness values and mechanismsavailable in the market produced by some companies have been offered for sale, they have not been fullymechanized. It is estimated that the pepper harvest mechanisms can still be improved. The increasing importanceof harvesting mechanisms has created the need to continue such studies in our country.
Keywords: Tarımsal Ekonomi ve Politika; Ziraat Mühendisliği; Bahçe Bitkileri; Bitki Bilimleri; Ziraat; Toprak Bilimi; Balıkçılık; Su Kaynakları; Gıda Bilimi ve Teknolojisi